One pot synthesis of monodisperse Fe3O4 nanocrystals by pyrolysis reaction of organometallic compound - Chiu, W.S.; Radiman, S.; Abdullah, M.H.; Khiew, P.S.; Huang, N.M.; Abd-Shukor, R. (Elsevier, 2007)
This paper reports on a simple and reproducible technique to prepare high quality colloidal Fe3O4 nanocrystals (NCs) with controlled size, shape and narrow size distribution without any size sorting process. The method is based on the pyrolysis of self-made iron oleate precursor by using oleic acid which was extracted from natural palm-oil as capping ligands. By controlling the growth time, the size of the NCs can be tuned within the range of 4-18 nm diameter with a standard deviation less than 18 of the mean diameter. TEM micrograph shows that NCs are highly monodisperse and spherical in shape. By controlling the evaporation of the solvents, the NCs self-assembled into monolayer and bi-layer into triangle "island" in an ordered hexagonal closed-packed superlattices. X-ray diffraction (XRD) pattern reveals that all the peaks of the NCs can be indexed with the standard sample. Measurements from vibrating sample magnetometer (VSM) showed that the magnetic properties correlate directly with the size of the NCs. Â© 2007 Elsevier B.V. All rights reserved.